A Lexical Approach to Identifying Dimensions of Organizational Culture - Chapman, Derek S.; Reeves, Paige; Chapin, Michelle (Frontiers in Psychology, 2018)
A comprehensive measure of organizational culture was developed using a lexical approach, a method typically employed within the study of personality. 1761 adjectives were narrowed down and factor analyzed, which resulted in the identification of a nine factor solution to organizational culture, including the dimensions of: Innovative, Dominant, Pace, Friendly, Prestigious, Trendy, Corporate Social Responsibility, Traditional, and Diverse. Comprised of 135 adjectives most frequently used in describing organizational culture by current employees of several hundred organizations, the Lexical Organizational Culture Scale (LOCS) was found to predict employee commitment, job satisfaction, job search behaviors, and subjective fit better than earlier scales of organizational culture. The study demonstrates that organizational culture measured using a lexical approach such as LOCS was a significant improvement to measuring Organizational Culture using traditional anthropomorphic measures of organizational culture. Scales for each of the nine factors identified in the lexical study are developed and validated.